Fishy Business? A Case Study on Ecologically Unequal Exchange in Norwegian Aquaculture - Kirkedam,Marie Heglum (2024)
The current climate crisis is pressuring policymakers to outline what a post-fossil economy might entail. In Norway, many have pointed towards the salmon farming industry as a central part of the country’s green transition. At the same time, the industry has shifted towards increasing use of feed imports from Brazilian soy plantations - the second largest driver of deforestation in the country. Exploring this contradiction, this thesis aims to analyse to what extent the theoretical framework of ecologically unequal exchange (EUE) can explain the Brazilian-Norwegian trade in soy for salmon. EUE challenges neoclassical trade theory by positing that the prevailing free trade regime allows for a structural transfer of biophysical resources from peripherical to core countries – enabling environmental degradation in the first and enhancing industrial capacity in the latter. Using a methodology based on life cycle analysis, an asymmetrical flow of the biophysical resources is observed when applied to the abovementioned trade relation.
Keywords: Ecologically Unequal Exchange; Aquaculture; Norway